Evolutionary medicine - Stearns, Stephen C. (Henry Stewart Talks, 2023)
Evolutionary medicine, Mismatch, trade-offs and large numbers in evolution, Pathogen evolution, The integration of life history theory with endocrinology and immunobiology, The connection between invasive placentas and cancer metastasis, Phage therapy, Strategies for antibiotic resistance, Evolution of SARS-CoV-2